Urgensi Pengaturan Akta Pembatalan Terhadap Akta Pejabat Pembuat Akta Tanah (PPAT) - Ni Made Nita Pradnyaning Putri; I Wayan Novy Purwanto (Jurnal Interpretasi Hukum, 2024)
When executing his responsibilities to authenticate deeds within the realm of land transactions, it is quite frequent for a PPAT to face issues concerning previously executed deeds, particularly when parties demand their annulment. This study addresses the lack of normative guidelines pertaining to the specific forms or types of cancellation deeds required to annul a PPAT deed. This study aims to explore the imperative of instituting regulatory measures concerning the annulment deeds executed by PPAT, as well as the legal consequences that arise from the nullification of a PPAT Deed. Utilizing a normative legal research approach that emphasizes statutory analysis, the study scrutinizes the legal structures outlined in diverse legislative documents. The methodological approach involved the utilization of library research or document analysis to collect legal documentation, which was subsequently subjected to qualitative evaluation. The results of the study demonstrate that the establishment of a Deed of Cancellation for a PPAT Deed by a Notary, or in their presence, is authorized according to Article 15, Paragraph (2), sub-paragraph f of the UUJN-P. This authorization is intended to provide legal assurance to all relevant parties and Land Deed Making Officials, given the lack of detailed regulations specifying the nature, structure, content, and procedural stipulations required for these cancellations. Consequently, the legal repercussions of canceling a PPAT Deed are that all entities and individuals are returned to their original state prior to the execution of the PPAT Deed.